Ultraestructura e histoquímica de dos tipos de glándulas mucosas de la piel de cryptobatrachus (amphibia, anura) (1985)
The skin of the middorsal region of the trunk of  Cryptobatrachus is studied here. The skin is characterized by light microscopy electron microscopy (TEM), and by histochemical test. These, means support a conclusion that two types of mucous glands are present. These are termed here Gland G2. The former is common among frogs but the latter (G2) is described for the first time. G2 mucous glands possibly contribute secretions used in holding the eggs and developing embryos on the skin of the dorsum in those frogs which incubate their- young on the back of the females.